Phytochemical profiling and anticancer activity of the n-butanol fraction from Ardisia villosa extract: Inhibition of gastric cancer cell proliferation via cell cycle arrest and senescence induction - Nguyet Mai Hua; Van Khang Pham; Thi Thanh Huong Le; Son Hiep Pham; Viet Hoang; Thu Huong Trinh; Dinh Quang Hung Can; Van Hung Hoang; Phu Hung Nguyen (PLoS ONE, 2026)
Medicinal plants serve as valuable sources for anticancer drug discovery. This study investigated the anticancer potential of the n -butanol fraction from Ardisia villosa extract against breast and gastric cancer cell lines. Phytochemical profiling using UPLC-QToF-MS in both positive and negative ESI modes identified 118 putative compounds, including flavonoids, lignans, alkaloids, triterpenoids, steroids, coumarins, and phenolic acids. The n -butanol fraction exhibited dose-dependent antiproliferative effects, with IC 50 values of 60.2 µg/mL (MCF-7), 85.2 µg/mL (MKN45), and 51.7 µg/mL (AGS). In AGS gastric cancer cells, the extract significantly inhibited 3D tumorsphere formation and suppressed cell migration at concentrations as low as 50 µg/mL (p < 0.001). Additionally, n -butanol fraction extract markedly induced cellular senescence (p < 0.01). Mechanistic investigations revealed that the extract induced G 0 /G1 phase arrest by downregulating critical cell cycle regulators, including CCND1, CCNE1, CDK2, CDK3, CDK6, CDK8, and CDK9, while upregulating tumor suppressor and senescence-related genes such as p21, p53, p16, and p27 (p < 0.01). Molecular docking analyses further supported these findings by demonstrating strong binding affinities of phytochemicals to key cell cycle regulatory proteins, suggesting a direct molecular basis for their antiproliferative effects. In conclusion, the n -butanol fraction of Ardisia villosa displays potent anticancer activity, particularly in gastric cancer cells, through multi-targeted mechanisms involving cell cycle inhibition and senescence induction, and holds promise as a natural source for future anticancer therapeutics.